EDUKASI TENTANG PERTOLONGAN PERTAMA LUKA BAKAR PADA REMAJA - Fatmawati, Atikah; Sari, Ike Prafita (JURNAL PENGABDIAN MASYARAKAT KESEHATAN (ABDIMAKES), 2025)
Burns are a type of injury that can cause significant physical, psychological, and social impacts on sufferers. The facts in society reveal that several incorrect first aid practices for burns persist, including applying toothpaste and soy sauce to the wound. The purpose of this activity is to provide health education about first aid for burns to adolescents. This activity was conducted by a team of lecturers and students from Majapahit Health Sciences College as part of a community service initiative to enhance adolescents' knowledge of first aid for burns. The partner for this community service activity was Madrasah Aliyah Hikmatul Amanah Pacet Mojokerto. The method used was a lecture using leaflets and PowerPoint media, conducted for 45 minutes in the hall. The material presented was the definition of burns, causes of burns, degrees/stages of burns, and first aid for burns. The results of this activity received a positive response from the target participants. The results showed that before health education was provided, most individuals were in the good category (66%), and after the health education was provided, almost all were in the good category (88%). Through this activity, students' knowledge can increase, and the information they obtain can be applied in everyday life.